The house swap : a novel - Fleet, Rebecca (Pamela Dorman Books/Viking, 2018)
"A hypnotic domestic noir novel in which a house swap becomes the eerie backdrop to a crumbling marriage, a torrid affair, and the fatal consequences that unfold. Be careful who you let in. When Caroline and Francis receive an offer to house swap--from their city apartment to a house in a leafy, upscale London suburb--they jump at the chance for a week away from home, their son, and the tensions that have pushed their marriage to the brink. As the couple settles in, the old problems that permeate their marriage--his unhealthy behaviors, her indiscretions--start bubbling to the surface. But while they attempt to mend their relationship, their neighbor, an intense young woman, is showing a little too much interest in their activities. Meanwhile, Caroline slowly begins to uncover some signs of life in the stark house--signs of her life. The flowers in the bathroom or the music might seem innocent to anyone else--but to her they are clues. It seems the person they have swapped with is someone who knows her, someone who knows the secrets she's desperate to forget"--